Design of a multi-band low-profile antenna - Lim, Min (2018)
This final year project report illustrates the process of designing a multi-band low profile antenna that can operate over the frequency range from 400 MHz to 6 GHz for Unmanned Aerial Vehicle (UAV) applications using the ANSYS HFSS software. Antenna parameters as well as various design factors such as the type of substrate materials used, the feeding scheme and the dimensions of the antenna were studied. Upon designing and running the simulations, the results obtained were also discussed and analyzed.